Lichen Planus - A Clinicopathological Correlation from a Tertiary Care Institute in Chhattisagrh - Agarwala, Manoj Kumar; Agarwala, Pragya; Chandrakar, Karan (International Journal of Innovative Research in Medical Science, 2019)
Background: Lichen planus is a mucocutaneous disorder of unknown aetiology with mucosal involvement seen in 30-70% of cases. Histopathology is a reliable tool to diagnose lichen planus and differentiate it from other lichenoid eruptions. Methodology: 103 patients aged ≥18 years consecutively attending the outpatient clinic with clinical features suggestive of cutaneous and/or oral LP were recruited. A detailed data collection proforma including the demographic details was filled and clinical examination was done. The diagnosis of LP was confirmed by biopsy. An attempt to study the clinico-pathological correlation was made. Results: We studied 103 patients of lichen planus with ages ranging from 18- 77 years with the mean age being 45.8 years. In males, the peak prevalence was between the ages of 35-44 years while in the females, it was in the range of 45-54 years. There was no gender predilection in our study. Conclusion: Hypertrophic and classical types of CLP, and reticular and erosive types of OLP were common patterns in our study population. There was agreement between the clinician and the pathologist in 85% of cases.